The Relevance of Safar Law for Women Without Mahram to Family Economic Independence in the Era of Society 5.0 - Kristiane, Desy; Hidayatullah, Muhammad Syarief (Al-Mujtahid: Journal of Islamic Family Law, 2024)
In the era of Society 5.0, women have many opportunities and facilities if they want to strengthen their family's economic independence. However, a law prohibits women from traveling without a mahram. Many hadith texts prohibit women from traveling without a mahram, which are contradictory and have multiple interpretations, making the law of women traveling different opinions. This article will analyze the law and whether it is still relevant if it is associated with the demands of economic independence in the era of Society 5.0 by using a qualitative descriptive method approach to produce a legal analysis and get a new conclusion. It can be concluded that the law regarding the prohibition of women traveling without a mahram is broadly divided into two, namely prohibiting absolutely and detailing the law in two circumstances, namely related to interests or needs and safety factors. Then, the many positive opportunities and conveniences in this Society 5.0 era make it easier for women to implement the law regarding the prohibition of traveling without a mahram and make it relevant even in this advanced era.